Redescription of the pupa of Paryphoconus oliveirai Lane (Diptera: Ceratopogonidae) from Brazil - Ronderos, Maria Marcela (2007)
The pupa of Paryphoconus oliveirai Lane is described from a specimen collected from a sandy bottom of a shallow human disturbed stream near Manaus, Brazil. The pupa of P. oliveirai is compared with previous descriptions of the pupa of this species and with the pupae of its congeners, P. flavidus (Johannsen), and P. mayeri Wirth.